PENGELOLAAN LKP PADA MASA PENDMIK COVID-19 - Zhahara Yusra; Rufran Zulkarnain; Sofino Sofino (UNIB Press, Universitas Bengkulu, 2021)
The purpose of this study was to determine and describe in detail the management of LKP during the pandemic. This research is a qualitative descriptive research. This study uses interview data collection techniques, observation, and documentation. Data validity checking used time triangulation, subject triangulation and technical triangulation. The result of the research was that in the process of curriculum adjustment involving Mrs. Rosilah as the head of the LKP, Mr. Erwin as the curriculum organizer and Mrs. Leni Susanti as the tutor, curriculum adjustments were made in the form of dividing study groups into 2x a week, there was no change in instructors in the learning process, changes working hours in accordance with face-to-face changes, and the application of health protocols in the face-to-face learning process and during the implementation of competency exams.